2022
DOI: 10.1001/jamanetworkopen.2022.45141
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Radiomics in Differentiating Histologic Subtypes of Epithelial Ovarian Carcinoma

Abstract: ImportanceEpithelial ovarian carcinoma is heterogeneous and classified according to the World Health Organization Tumour Classification, which is based on histologic features and molecular alterations. Preoperative prediction of the histologic subtypes could aid in clinical management and disease prognostication.ObjectiveTo assess the value of radiomics based on contrast-enhanced computed tomography (CT) in differentiating histologic subtypes of epithelial ovarian carcinoma in multicenter data sets.Design, Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…29 Radiomic analysis also proved to have a high AUC-ROC in detecting epithelial ovarian carcinoma subtypes on CT with AUCs or 0.836. 30 In contrast to most of such studies, our study has achieved AUC-ROCs of 0.95 in detecting the histological subtype of NSCLC. Moreover, these studies have extracted variable numbers of features ranging from 107 to 1160 radiomic features, using 3D-Slicer and MATLAB to do so.…”
Section: Performance On Squamous Cellmentioning
confidence: 61%
“…29 Radiomic analysis also proved to have a high AUC-ROC in detecting epithelial ovarian carcinoma subtypes on CT with AUCs or 0.836. 30 In contrast to most of such studies, our study has achieved AUC-ROCs of 0.95 in detecting the histological subtype of NSCLC. Moreover, these studies have extracted variable numbers of features ranging from 107 to 1160 radiomic features, using 3D-Slicer and MATLAB to do so.…”
Section: Performance On Squamous Cellmentioning
confidence: 61%
“…Notably, the inclusion of wavelet features in our modeling approach aligns with the ndings of previous studies. 13,14,15 Wavelet transform enables the extraction of multi-frequency and multi-scale image information, making it particularly useful for capturing complex clinical characteristics that cannot be easily described by simple visual features of tumor images. The highdimensional abstract nature of wavelet features may serve a crucial role in capturing clinical information that may not be readily apparent to the naked eye.…”
Section: Discussionmentioning
confidence: 99%
“…The highdimensional abstract nature of wavelet features may serve a crucial role in capturing clinical information that may not be readily apparent to the naked eye. 15 It is worth mentioning that, among the selected features, all but two of them are high-order textures that provide valuable insights into the distribution of pixel points. This characteristic indicates that high-order textures are more effective in re ecting the spatial heterogeneity changes associated with MLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large study including 1329 patients with ovarian tumours provided an AUC of 0.91 of the machine-learning-based radiomics model for the differentiation between the benign and malignant tumours on contrast-enhanced CT [150]. Furthermore, a multicentric study involving 665 patients from four centres reported an AUC of 0.836 for differentiating high-grade and non-high-grade serous carcinoma [151].…”
Section: Ctmentioning
confidence: 99%